Analysis of a Phase 2b Study of GEN-003, a Genital Herpes Immunotherapy, Showed Significant Reductions in Viral Shedding and Lesion Rate Vs Placebo. (4th October 2017) - Heineman, Thomas C; Bernstein, David; Wald, Anna; Van Wagoner, Nicholas; Leone, Peter; Mayer, Kenneth; Lucksinger, Gregg; Win, Sandra; Koltun, William; Desai, Nisha; Oliphant, Thomas; Natenshon, Andrew; et al.
Abstract: Background: GEN-003 is an investigational genital herpes immunotherapy comprising gD2ΔTMR, an HSV-2 antigen that induces neutralizing antibody and T cell responses, ICP4.2, an HSV-2 T cell antigen selected through human T cell screens, and Matrix-M2™, a saponin-based adjuvant. This Phase 2b study was designed to evaluate efficacy and safety of GEN-003 vs. placebo. Methods: Healthy persons, age 18–50 years, with 3–9 HSV-2 genital herpes outbreaks annually were randomized to 3 groups: placebo, or 60 µg of each antigen combined with 50 µg (60/50 group) or 75 µg (60/75 group) of adjuvant, administered 3 times 21 days apart. Study endpoints included safety, immunogenicity, HSV-2 shedding frequency, lesion rate and recurrence frequency. Viral shedding was measured from anogenital swabs by PCR. Swabs were collected for 28 days at baseline, and after the third dose, 6 months and 1 year. The presence of herpes lesions was recorded daily by electronic diary. Results: One hundred and thirty-one participants enrolled and >90% received all 3 doses. In the 28-day post-treatment period, viral shedding was reduced by 40% and 27% in the 60/50 and 60/75 groups, respectively, compared with a 5% increase in the placebo group. At 6 months post-treatment, median lesion rates were significantly lower in the 60/50 and 60/75 groups (2.7% and 1.9%, respectively) vs. the placebo group (5.6%, p < 0.05), resulting in median reductions of 52% and 66%. In participants not receiving suppressive antivirals, the median recurrence frequency was 1.0/6 months in the 60/50 group vs. 2.0 in the placebo group (p = 0.08). The median recurrence duration in the 60/50 group was lower than in the placebo group (2.8 vs. 4.2 days; p < 0.05). The most commonly reported adverse events (AEs) following GEN-003 vaccination were injection site pain/tenderness (97%), fatigue (82%), headache (82%) and myalgia (80%). No vaccine-related serious AEs, autoimmune events or other AEs of special interest were reported. Conclusion: In adults with recurrent genital herpes, GEN-003 reduced HSV-2 shedding frequency, genital herpes lesion rate, recurrence frequency and recurrence duration through 6 months after the last dose. Local and systemic symptoms were common in GEN-003 recipients, but treatment completion was high with few discontinuations due to AEs. Disclosures: T. C. Heineman, GSK group of companies: Consultant and Shareholder, Consulting fee; D. Bernstein, Genocea Biosciences: Consultant and Investigator, Consulting fee and Research support; A. Wald, Genocea Biosciences: Investigator, Research grant and Support for travel to meetings for the study; N. Van Wagoner, Genocea Biosciences: Consultant, Research support and Travel support to present at scientific meetings; P. Leone, Genocea Biosciences: Grant Investigator and Scientific Advisor, Consulting fee, Research grant and Speaker honorarium; T. Oliphant, Genocea Biosciences: Consultant, Consulting fee; A. Natenshon, Genocea Biosciences: Employee, Salary; L. K. McNeil, Genocea Biosciences: Employee, Salary; J. B. Flechtner, Genocea Biosciences: Employee, Salary; S. Hetherington, Genocea Biosciences: Employee, Salary